Analysis of the Effect of Brand Image, Service Quality and Purchase Interest on Purchase Decisions: (Study on S26 Procal and Promise Gold Powdered Milk Consumers on Hypermarket Channels in Jakarta Distribution Area) - Hamsinah Hamsinah (Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the analysis of the influence of brand image, service quality and purchase intention on purchasing decisions (Study on Consumers of S26 Procal and Promise Gold Powdered Milk at Chanel Hypermarkets in Jakarta Distribution Area). This study took a population of consumers of S26 Procal and Promise Gold milk powder at the Chanel Hypermarket in the Jakarta Distribution Area, amounting to 1,511 people, while the sample used was using slovin calculations where from the population only took a sample of 94 respondents with an error rate of 10%, variable The research consists of independent variables or independent variables (X), namely brand image (X1), service quality (X2) and buying interest (X3) while the dependent variable or dependent variable (Y) is purchasing decisions. The research method is using quantitative methods and the number of statement items is 40 which consists of a list of statements related to brand image variables (X1), service quality (X2), buying interest (X3) and purchasing decisions (Y), each of which is 10 statement items. The measurement scale used is a Likert scale from 1-5 with 5 categories. The data analysis technique used in this research is descriptive and linear regression test. The results of data analysis show that the multiple linear regression equation is Y = 0.627 + 0.434 (X1) + 0.279 (X2) + 0.279 (X3). The correlation coefficient Rx123 is 0.589 and is in the range 0.40 – 0.599 with a moderate level of relationship, meaning that the influence of brand image (X1), service quality (X2) and buying interest (X3) on purchasing decisions (Y) is included in the medium category. While the Adjusted R Squar coefficient of determination of 0.325 shows that brand image (X1), service quality (X2) and buying interest (X3) contribute to purchasing decisions (Y) by 32.5% and the remaining 67.5% is influenced by other factors. In the simultaneous hypothesis test, the Fcount value 15.935>Ftable 2.14 or the probability value Sig 0.000 <0.05, then Ho is Rejected and Ha is accepted, thus the proposed hypothesis stipulates that there is a positive and significant influence between brand image (X1), service quality (X2) and buying interest (X3) on purchasing decisions (Y) on S26 Procal and Promise Gold Powdered Milk Consumers at Chanel Hypermarkets in the Jakarta Distribution Area